A Narrative Study of Pre-Service English Teachers' Perspective on Code-Switching Activities in Their Speaking Class - Zahiroh, Muniatuz; Setyono, Budi; Sukmaantara, I Putu (International Journal of Qualitative Research, 2024)
The majority of Indonesians can speak two or more languages. Code-switching is the practice of language changing or switching to another, which is highly widespread in bilingual and multilingual communities like Indonesia. Code-switching is a phenomenon that also happens throughout the teaching process in ELT classrooms. English is chosen as the medium of instruction in several contexts in Indonesia. One of the contexts is when pre-service English teachers use English as their primary language of teaching. The study aims to explore pre-service English teachers’ perspectives on code-switching in their Speaking classes. The study was performed at the English Education Department in one of the state universities in Jember, Indonesia. An interview was utilized to generate the data. Three pre-service English teachers were voluntarily taken as the participants. The data were analyzed using Thematic Analysis. There were three key perceptions identified from the participants' responses, namely positive attitude, negative attitude, and suggestion on code-switching implementation.